Assessing the reproducibility of microbiome measurements based on concordance correlation coefficients. Issue 4 (11th June 2021) - Cui, Ying; Peng, Limin; Hu, Yijuan; Lai, HuiChuan J.
Abstract: Evaluating the reproducibility or agreement of microbiome measurements is often a crucial step to ensure rigorous downstream analyses in microbiome studies. In this paper, we address this need by developing adaptations of Lin's concordance correlation coefficient (CCC) tailored to microbiome studies. We introduce a general formulation of the new CCC measures upon the use of a distance function appropriately characterizing the discrepancy between microbiome compositional measurements. We thoroughly study the special cases that adopt the Euclidean distance and Aitchison distance. Our proposals appropriately account for the unique features of microbiome compositional data, including high‐dimensionality, dependency among individual relative abundances and the presence of many zeros. We further investigate a practical compound approach to help better understand the sources of data inconsistency. Extensive simulation studies are conducted to evaluate the utility of the proposed methods in realistic scenarios. We also apply the proposed methods to a microbiome validation data set from the Feeding Infants Right.. from the STart (FIRST) study. Our analyses offer useful insight about the extent of data variations resulted from two different experiment procedures as well as their heterogeneous patterns across genera.